A collaborative ide for graphics programming - Ubalde Enriquez, Rembrandt (2020)
We present a collaborative coding environment that helps the teaching of introductory computer graphics courses, with the goal of to do teaching graphics fundamentals more effectively and lowering the excessive difficult of initiate into 3D graphics programming. Traditionally, the OpenGL Library is used for teaching computer graphics courses, since there are bindings for the most popular languages, including Python, Ruby, Java and the web (WebGL). In particular, our proposed framework provides a web IDE for collaborative coding, between classmates or workgroups, and the professor can help them or interact on it. The second component is the use of the Emscripten library, which allows the program with OpenGL on the web in the same way as it is done in a local mode. Compared with WebGL, our proposal has better benefits since the code could be used in any computer with OpenGL support, which has greatly benefited our students. It also was proposed to diminish the complexity of creating websites with 3D graphics support and better online games, which has been motivating students to learn 3D computer graphics, build educational graphical applications and articles, host them online. Compared to other online coding platforms, oriented to mainstream graphics educational materials and graphics in general, the collaborative IDE for programming computer graphics that we have developed offers the possibility of students could learn OpenGL in a fast way for both inside and outside our classrooms with the C++ language.